Soil carbon and fertility attributes in response to surface liming under no‑tillage - Briedis, Clever; Sá, João Carlos de Moraes; Caires, Eduardo Fávero; Navarro, Jaqueline de Fátima; Inagaki, Thiago Massao; Ferreira, Ademir de Oliveira (Pesquisa Agropecuaria Brasileira, 2012)
The objective of this work was to evaluate the effect of surface liming on the content of total organic carbon (TOC) of a soil under no‑tillage, and to identify the relationship between that content and other fertility attributes. The experiment was carried out on a medium‑textured Oxisol in Ponta Grossa, PR, Brazil. The treatments consisted of the application of 0 and 6 Mg ha‑1 of dolomitic lime on soil surface in 1993 and of the reapplication of 0 and 3 Mg ha‑1 in 2000, on plots with or without lime. The soil was collected in 2008, and the TOC content and fertility attributes were evaluated. Liming increased TOC content and base saturation, and decreased aluminium saturation. TOC content showed a linear relation with the effective cation exchange capacity and correlation with the levels of P and K. The potential CEC showed correlation with TOC, and the effective CEC with pH. Liming under no‑tillage, for a long period of time, increases TOC and total N contents.